COUNTERHEGEMONIC DISCOURSE IN TENGKU AMIR HAMZAH’S POEM MABUK - Bima Prana Chitra; Ikhwanuddin Nasution; Asmyta Surbakti; Muhizar Muchtar (Universitas Islam Sumatera Utara (UISU), 2018)
The research aims to implement the theory of Counterhegemonic discourse with two points of discussion: the Dutch Colonial’s Social Exclusivism and Reintroducing Indonesian Cultural Identity in Mabuk, a lyric poem written by Tengku Amir Hamzah during the Dutch colonialization of Indonesia (Dutch East Indies). The poem consists of both traditional Malay rhyming scheme and modern Indonesian language structure that embody Tengku Amir Hamzah’s emotional response, as well as his romantic expressions towards the state of a drunken person in metaphorical nuance with the points of inciting nationalism. The study was conducted by means of descriptive qualitative method utilizing critical discourse analysis (CDA) method with the support of deconstruction theory and phenomenological approach. The result shows that Mabuk is a Counterhegemonic poem revealing the standing of the Dutch during the colonialization era and the fading of cultural identity which is to be restored in order to get harmony in national existence.